The brain-placental axis: Therapeutic and pharmacological relevancy to pregnancy. (November 2019) - Behura, Susanta K.; Dhakal, Pramod; Kelleher, Andrew M.; Balboula, Ahmed; Patterson, Amanda; Spencer, Thomas E.
Graphical abstract: Abstract: The placenta plays a critical role in mammalian reproduction. Although it is a transient organ, its function is indispensable to communication between the mother and fetus, and supply of nutrients and oxygen to the growing fetus. During pregnancy, the placenta is vulnerable to various intrinsic and extrinsic conditions which can result in increased risk of fetal neurodevelopmental disorders as well as fetal death. The placenta controls the neuroendocrine secretion in the brain as a means of adaptive processes to safeguard the fetus from adverse programs, to optimize fetal development and other physiological changes necessary for reproductive success. Although a wealth of information is available on neuroendocrine functions in pregnancy, they are largely limited to the regulation of hypothalamus–pituitary–adrenal/gonad (HPA/ HPG) axis, particularly the oxytocin and prolactin system. There is a major gap in knowledge on systems-level functional interaction between the brain and placenta. In this review, we aim to outline the current state of knowledge about the brain-placental axis with description of the functional interactions between the placenta and the maternal and fetal brain. While describing the brain-placental interactions, a special emphasis has been given on the therapeutics and pharmacology of the placental receptors to neuroligands expressed in the brain during gestation. As a key feature of this review, we outline the prospects of integrated pharmacogenomics, single-cell sequencing and organ-on-chip systems to foster priority areas in this field of research. Finally, we remark on the application of precision genomics approaches to study the brain-placental axis in order to accelerate personalized medicine and therapeutics to treat placental and fetal brain disorders.